IGRF-13 model-based analysis of global long-term variation of main magnetic field - Chuyue Zhou; Hanxian Fang; Die Duan; Chao Xiao; Ganming Ren; Hongtao Huang; Yang Lin (地球与行星物理论评)
The geomagnetic field is a natural barrier to protect the Earth and maintain the stability of the Earth's environment, and is widely used in various fields as an important strategic resource. Many studies indicated that the changes in the geomagnetic field have intensified in recent years. This study uses the 13th generation of the International Geomagnetic Reference Field model (IGRF-13) to investigate the long-term changes in the Earth's main magnetic field from 1900 to 2020 and analyzes the evolution of the South Atlantic Anomaly (SAA). The results show that, the main magnetic field exhibits an increasing trend in the Eastern Hemisphere, while its variations in the Western Hemisphere are more diverse. The Earth's dipole moment is decreasing while the non-dipole moment is increasing in the last 120 years, which means the contribution from dipole (non-dipole) field is decreasing (increasing). The average westward drifting speed of the main field is 0.2°/a since 1900, with the anomaly field exhibiting a predominant westward drift direction, complemented by a modest north-south oscillation. In the horizontal direction, the focuses of the main magnetic field gradient anomalies exhibit a slow variation in the Northern Hemisphere, whereas in the Southern Hemisphere, they demonstrate a more rapid westward drift accompanied by a slight north-south oscillation. Since around 1930, when the African anomaly formed, the zero contours of the latitudinal gradient in Africa and the South Atlantic have shifted southward and westward rapidly. The magnetic poles change more rapidly relative to the geomagnetic poles, and the direction and speed of movement differ in the Northern and Southern Hemispheres: in the Northern Hemisphere, the magnetic poles have crossed from the Western Hemisphere to the Eastern Hemisphere, while in the Southern Hemisphere, the poles have moved toward lower latitudes. The SAA represents the weakest region of the Earth's main magnetic field, and a comparison between its western primary minimum and the eastern secondary minimum, which emerged in 2007, reveals a notable low value of approximately 103 nT. Although the magnetic field strength in the SAA region exhibits an overall declining trend, the discrepancy between the primary and secondary minima has been progressively diminishing annually. Furthermore, the primary minimum center has demonstrated a general southwestward drift trajectory over the past 120 years, while the secondary minimum center has exhibited an eastward shift with a subtle north-south oscillation since 2007.